Pharmacological treatment of atypical hemolytic-uremic syndrome. (February 2014) - Vester, Udo; Mache, Christoph J
<x xml:space="preserve">Abstract</x> Introduction: Atypical hemolytic-uremic syndrome (aHUS) is a rare and devastating form of thrombotic microangiopathy (TMA) predominantly affecting the kidneys. It has to be differentiated from Shigatoxin-associated HUS, thrombotic-thrombocytopenic purpura and secondary forms of HUS. In most cases, aHUS is characterized by a systemic dysregulation in the alternative pathway of complement activation, leading to a complement attack, for example, on host renal endothelial cells and renal TMA. Areas covered: The role of the complement system, the natural course of aHUS and previous treatment options including plasma therapy are presented. During recent years, eculizumab, a humanized monoclonal antibody targeting complement component C5, has been increasingly used in the treatment of aHUS. A literature review was conducted using the PubMed database with search terms 'eculizumab' and 'atypical hemolytic-uremic syndrome, ' and further resources were identified by review of relevant reference lists. The results of two prospective trials as well as case reports and retrospective studies are reviewed. Expert opinion: Eculizumab is highly effective and superior to plasmatherapy in the prevention and treatment of aHUS episodes. Earlier initiation of eculizumab in an aHUS manifestation is associated with greater improvement of renal function. Important issues including optimal duration of eculizumab treatment, strategies to prevent or treat posttransplant recurrence, additional treatment options in autoimmune aHUS and possible indications for eculizumab in end-stage renal failure are discussed.